Postmodernism, reason and religion - Gellner, Ernest (Routledge, 1992)
Explores the ideological options open to modern society by considering the three main visions influential at present: Religious fundamentalism; Permissive relativism; and a liberalism commited to the idea of the uniqueness of truth, without claiming to possess it.